Validation of a multi-phase plant-wide model for the description of the aeration process in a WWTP. (1st February 2018) - Lizarralde, I.; Fernández-Arévalo, T.; Beltrán, S.; Ayesa, E.; Grau, P.
Abstract: This paper introduces a new mathematical model built under the PC-PWM methodology to describe the aeration process in a full-scale WWTP. This methodology enables a systematic and rigorous incorporation of chemical and physico-chemical transformations into biochemical process models, particularly for the description of liquid-gas transfer to describe the aeration process. The mathematical model constructed is able to reproduce biological COD and nitrogen removal, liquid-gas transfer and chemical reactions. The capability of the model to describe the liquid-gas mass transfer has been tested by comparing simulated and experimental results in a full-scale WWTP. Finally, an exploration by simulation has been undertaken to show the potential of the mathematical model. Graphical abstract: Highlights: Validation of multi-phase plant wide model for liquid-gas transfer description. Aeration system efficiency estimation. Calibration and validation of the aeration process.